Kualitas Pelayanan Publik dalam Pengurusan E-KTP di Kecamatan Medan Baru Kota Medan - Lubis, Fatimah; Suharyanto, Agung; Batubara, Beby Masitho (Mahesa Research Center, 2025)
Public services are services provided by the government as a state administrator to the community, the Electronic Identity Card is an identity card that must be owned by every Indonesian citizen which contains a clear number, name, place/date of birth, gender, clear address along with RT/RW, village/village, sub-district, religion, marital status, occupation, citizenship, and the validity period of the ID card, The purpose of this study is to determine the quality and obstacles of employee service in making Electronic KTP in Medan Baru District, Medan City, by using qualitative research methods, this research focuses on Medan Baru District, the techniques used in this study are interviews, observations, and documentation in data collection, the performance of the State Civil Apparatus is guided by the Standard Operating Procedures in Medan Baru District and has been applied from In 2017 until now, there is a lack of blanks from the central government, a lack of clear information for the public and limited electronic ID card recording tools, the conclusion of the Electronic ID card contains security codes and electronic recordings as a means of verifying and validating a person's identity data.